Effect of a modified energy density equation to achieve a more uniform energy input during LPBF for improved repeatability. (May 2022) - Dowling, L.; Kennedy, J.; Trimble, D.
Abstract: The main priority for additive manufacturing research must be an improvement in process repeatability and reproducibility. This paper proposes a modified energy density equation as a basis for location dependent control of process parameters. This equation was used to adapt the process parameters in laser powder bed fusion of cobalt chrome alloy to achieve a more uniform energy density input across the build. Using this modified equation, the standard deviation of the mechanical properties was reduced by 40%. This improvement in consistency was verified using additional testing using 316L. The reduction in the variation in local mechanical property values was verified to be statistically significant.